2022
DOI: 10.1209/0295-5075/ac8e92
|View full text |Cite
|
Sign up to set email alerts
|

Bistability-induced chimeras in one-dimensional paced excitable rings with nonlocal couplings

Abstract: In this paper, we provide a bistability-mechanism in giving rise to a new kind of chimeras in the one-dimensional (1D) paced nonlocally coupled excitable rings without rotational coupling scheme. It is exposed that the elements in the system can perform distinct modes and gives rise to the chimera pattern. By analyzing the response dynamics in the corresponding local excitable model with the same pacing, the initial-excitation-dependent bistability feature is revealed as the mechanism responsible for this chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Further investigations demonstrated that chimera or chimeralike states can also emerge in systems with purely local coupling [11], global coupling [12], adaptive coupling [13], time-varying coupling [14], hierarchical connectivities [15], and star structures [16], the single paradigmatic network models [17][18][19], such as small-world networks, Erdös-Rényi networks, and scale-free networks for typical examples, and even the multilayer networks [20]. Moreover, besides the initial coupled phase-oscillator systems, a variety of other systems with distinct local dynamics, such as time-delayed oscillators [21], discrete maps [22], continuous chaotic systems [23], limit-cycle elements [24], bursting neurons [25], bistable models [26], quantum systems [27], and excitable units [28] were shown to perform chimera or chimeralike behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations demonstrated that chimera or chimeralike states can also emerge in systems with purely local coupling [11], global coupling [12], adaptive coupling [13], time-varying coupling [14], hierarchical connectivities [15], and star structures [16], the single paradigmatic network models [17][18][19], such as small-world networks, Erdös-Rényi networks, and scale-free networks for typical examples, and even the multilayer networks [20]. Moreover, besides the initial coupled phase-oscillator systems, a variety of other systems with distinct local dynamics, such as time-delayed oscillators [21], discrete maps [22], continuous chaotic systems [23], limit-cycle elements [24], bursting neurons [25], bistable models [26], quantum systems [27], and excitable units [28] were shown to perform chimera or chimeralike behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…chimera states [18]. Chimera states are a special state in which coherent and incoherent states coexist in an identical system [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…With the in-depth research, many issues like effects of transient behaviors [20][21][22], time delay [23][24][25], phase lags [26], coupling functions [27][28][29][30][31], and the impacts of random perturbation and complex topology of coupling [32][33][34][35][36] have been solved, so the survival conditions of the chimera states have been continuously expanded. Then, it was discovered that the emergence of chimera states is not limited to the Kuramoto phase oscillators, but can also be observed in the Landau-Stuart and the Ginzburg-Landau systems [25,[37][38][39][40][41][42][43][44], chaotic maps [45], quantum oscillator systems [46,47], time-continuous Rssler [48,49], Lorenz [50], and neural networks such as Hodgkin-Huxley, FitzHugh-Nagumo, Integrate-and-Fire oscillators [51][52][53][54]. Besides widely numerical and theoretical studies, the experimental evidence on the chimera state has been presented in optical [55,56], chemical [57][58][59], mechanical [60], electronic ...…”
mentioning
confidence: 99%